Conjunctival mass as the initial presentation of acute lymphoblastic leukemia in a child - Jagdish Prasad Meena; Aakanksha Sharma; Aditya Kumar Gupta; Anuj Singh; Prafulla Kumar Maharana; Ravi Hari Phulware; Rachna Seth (Indian Journal of Medical and Paediatric Oncology)
Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy with excellent survival. ALL has varied presentations. Presentation of ALL as a conjunctival mass is very rare. We report a child who presented to us with redness of the left eye and was found to have conjunctival mass. On biopsy, this mass was later diagnosed as ALL. The bone marrow examination supported the diagnosis. Timely diagnosis and initiation of treatment are essential to salvage the vision and to improve survival in such cases.